Metabolic engineering of Clostridium autoethanogenum for selective alcohol production - Liew, Fungmin; Henstra, Anne M.; Kӧpke, Michael; Winzer, Klaus; Simpson, Sean D.; Minton, Nigel P. (Elsevier, 2017)
Gas fermentation using acetogenic bacteria such as Clostridium autoethanogenum offers an attractive route for production of fuel ethanol from industrial waste gases. Acetate reduction to acetaldehyde and further to ethanol via an aldehyde: ferredoxin oxidoreductase (AOR) and alcohol dehydrogenase has been postulated alongside the classic pathway of ethanol formation via a bi-functional aldehyde/alcohol dehydrogenase (AdhE). Here we demonstrate that AOR is critical to ethanol formation in acetogens and inactivation of AdhE led to consistently enhanced autotrophic ethanol production (up to 180%). Using ClosTron and allelic exchange mutagenesis, which was demonstrated for the first time in an acetogen, we generated single mutants as well as double mutants for both aor and adhE isoforms to confirm the role of each gene. The aor1+2 double knockout strain lost the ability to convert exogenous acetate, propionate and butyrate into the corresponding alcohols, further highlighting the role of these enzymes in catalyzing the thermodynamically unfavourable reduction of carboxylic acids into alcohols.